Eco-efficient concrete using industrial wastes: a review - Pacheco-Torgal, F. (2011)
Concrete is one of the most widely used construction materials in the world. However, the production of Portland cement as the essential constituent of concrete requires a considerable energy level and also releases a significant amount of chemical carbon dioxide emissions and other greenhouse gases (GHGs) into the atmosphere. Global demand will increase almost 200 % by 2050 from 2010 levels. Thus, seeking an eco-efficient and sustainable concrete may be one of the main roles that construction industry should play in sustainable construction. To make the concrete more eco-efficient, different life cycle phases of concrete products can be brought to bear such as extraction of raw material, production of constituents, production of concrete, transportation, erection, maintenance, demolition and recycling. Portland cement can be partially replaced by cementitious and pozzolanic materials especially those of industry by-products such as fly ash, GGBS, silica fume, ceramic waste powder and metamorphic rock dust form stone cutting industry. The aggregates are also conserved by replacing them with recycled or waste materials among which recycled concrete, ceramic waste, postconsumer glass, and recycled tires are the most used. This paper summarizes current knowledge about eco-efficient concrete, by reviewing previously published work.